Evaluasi Penambahan Temulawak (Curcuma xanthorriza Roxb.) terhadap Karakteristik Fisikokimia Silase Kulit Pisang Kepok: Evaluation of Javanese Turmeric (Curcuma xantorrhiza Roxb.) Addition) on the Physicochemical Properties of Kepok Banana Peel Silage - Apdila Safitri; Novrianus Gabriel; Ardiansyah; Anjani, Fandini Meilia (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
Banana peel contains fructooligosaccharide (FOS), which is useful as a prebiotic for the intestinal microflora of livestock, but easily rots. Banana peels were processed into silage with the addition of Javanese turmeric as a feed additive derived from herbal plants within 21 days of the ensilage process. The effect of Javanese turmeric addition on kepok banana peel silage was determined by its physicochemical characteristics. The study used a completely randomized design (CRD) with 4 treatments and 3 replications consisted of P0 (0% javanese turmeric + 4% EM4 + 6% molasses), P1 (1.5% javanese turmeric + 4% EM4 + 6% molasses), P2 (3% javanese turmeric + 4% EM4 + 6% molasses) and P3 (4.5% javanese turmeric + 4% EM4 + 6% molasses). The parameters observed were physical quality, fermentation quality, nutritional content, and water-soluble carbohydrate (WSC). The results showed that the addition of Javanese had no effect on the physical quality parameters and no significant effect on the fermentation quality, nutrient content, and water-soluble carbohydrate (WSC) in the kepok banana peel silage compared to the control treatment. It can be concluded that the addition of javanese turmeric to kepok banana peel silage does not alter its physical quality, fermentation quality, nutrient content, and water-soluble carbohydrate (WSC).